Functions and competences of people with disabilities in the context of training fashion designers - Riabchykov , M.; Lytvyn , O.; Nechipor, S.; Yehorov О. (Problems of Engineer-Pedagogical Education, 2020)
The article proves the possibility and expediency of using the matrix structure of competences to form the content of teaching people with disabilities in the process of training fashion designers. The combined use of the International Classification of Functions, Defects and Health, as well as the requirements of the Higher Education Standard for the specialty 182 "Light Industry", allowed us to form a system of descriptors which includes both the general descriptors recommended by the standard and the European Commission and the descriptors suggested by international standards for people with disabilities. The article identifies the main functions of the specialist in the field of the light industry and design, which in general include design, technological, managerial and business competence. For people with disabilities, these features need to be supplemented with additional functions which determine the overall abilities of these people in accordance with the International Classification of Functions, Defects and Health. As a result of the analysis of functions, competences and descriptors specific to people with disabilities, a matrix was formed that defines the peculiarities of their training. In contrast to the well-known Dublin descriptor system, the proposed matrix includes additional components that take into account the specific capabilities of people with disabilities determined, first, by their physical mobility and, second, by communication mobility. Such descriptors may, from the outset, include the use of products and technologies for personal indoor and outdoor transportation, communication with carers, basic and complex economic relationships, economic independence to determine competences and learning outcomes in the context of physical mobility. Communication mobility features that determine the education of people with disabilities may include clarifying the requirements for communication within formal and informal organizations, services, systems and insurance policies for persons providing financial support to people with disabilities. In the process of forming a system for training people with disabilities, the Kharkiv Fashion Cluster platform is actively used in conjunction with the Department of Technology and Design of Ukrainian Engineering Pedagogics Academy.